KENDALA DALAM PENYELESAIAN KREDIT MACET PADA PT. BANK PEMBANGUNAN DAERAH BALI CABANG DENPASAR. - Winata, Tri Aditya; Wiryawan, I Wayan; Rudy, Dewa Gde (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 01, Januari 2013)
As a financial intermediary organizations (financial intermendiary), the bank became amedia intermediary parties - parties who have surplus funds (surplus of fouds) theparties - parties that lack / need funding (lack of fouds). In common practice, problemloans, where credit facilities to customers who require credit problems which have lentcan not be paid back by the customer to the bank as agreed.
Keywords: Bank, customers, credit problems, legal.